Cumulative Component Damages on Collapse Capacity of Ductile Steel and CFT Moment Resisting Frames under Over-design Ground Motions. Issue 6 (26th April 2022) - Bai, Y.; Ma, X.; Wang, B.; Cao, G.; Beer, M.
ABSTRACT: Great earthquakes are likely to generate ground motions larger than those considered in design codes (over-design ground motions) and hence leading to a seismic demand that causes severe damages of structural components in general high-rise steel moment-resisting frames (SMRFs). Overall seismic behavior of high-rise SMRFs may be significantly affected by the local failure of members. This paper focuses on the margins of deterioration and collapse of 40-story SMRFs and the equivalent MRFs with concrete-filled tubular (CFT) columns considering the strength deterioration effect in constitutive models designed by current building standards. The input long-period ground motions are synthetic earthquake waves with flat velocity spectral shape. Deterioration and collapse criteria of models based on the peak ground motion velocity are estimated by performing the incremental dynamic analysis (IDA). The results indicate that the collapse mechanism was formed in the lower stories of high-rise SMRFs under the very rare earthquake. The strength and stiffness deterioration significantly amplified the damage extent and the influence degree depends on the sectional compactness of components. And the MRF with concrete-filled tubular (CFT) columns has a higher collapse margin against overall collapse compared with SMRFs.